2018
DOI: 10.1080/24750573.2018.1478192
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between attention deficit hyperactivity disorder and reelin gene polymorphisms in Turkish population

Abstract: PURPOSE: Although attention deficit hyperactivity disorder (ADHD) is one of the most frequently seen psychiatric disorders in childhood, its etiology and pathophysiology are not fully elucidated. The aim of the present study was to investigate the association between ADHD and RELN gene in Turkish children. METHOD: DNA samples were harvested from 102 patients with ADHD and 94 healthy controls. Three single-nucleotide polymorphisms of reelin gene (rs1270519, rs362691, and rs734147) were genotyped using real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Despite the fact that potential relationships between RELN gene abnormalities and several psychiatric disorders have been examined, only the link between ADHD and the RELN gene has been reported thus far. Kwon et al 17 26 observed a nonsignificant correlation between RELN rs362691 and RELN rs734147, whereas there was a significant correlation regarding RELN rs12705169 and the occurrence of ADHD among Turkish children.…”
Section: ■ Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the fact that potential relationships between RELN gene abnormalities and several psychiatric disorders have been examined, only the link between ADHD and the RELN gene has been reported thus far. Kwon et al 17 26 observed a nonsignificant correlation between RELN rs362691 and RELN rs734147, whereas there was a significant correlation regarding RELN rs12705169 and the occurrence of ADHD among Turkish children.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The high ranking of comorbidities and family aggregation in both conditions led the authors to hypothesize that comparable inherent aspects can be concerned with ADHD. 26 In autistic children, Reelin was reported as a likely genetic risk factor. Wang and colleagues postulated that RELN rs36269 could pose a greater risk of autism disorder than RELN rs736707 or GGC genetic repetition.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations